The Importance of Engaging in Scientific Research during Medical Training - Bhuiya, Tanzim; Makaryus, Amgad N. (International Journal of Angiology, 2023)
Many components of required skills and competencies exist, and are felt to contribute to the successful completion of training for independent practice in the medical field as a physician. These requirements are documented and detailed in a temporal fashion during the training period and used for advancement during training as well as documentation of successful completion of that training. While clinical skill development that allows optimal care and treatment of patients is of utmost importance during this training, other components of the training are important and contribute to the ideal development of a well-rounded and credentialed physician. One of these other components which is very important and needs to be recognized is the engagement of medical trainees across disciplines in academic and research scholarly activity. This engagement is an important component of medical training, and the development of skills and didactics geared toward efficient and accurate performance of research is essential.
Keywords: medical training; research; evidence-based medicine; scholarly activity; benefit